How Religious Leaders around the World Are Responding to the Covid-19 Pandemic - Yuli Andriansyah (Millah: Journal of Religious Studies, 2022)
The Covid-19 pandemic has presented significant challenges for religious leaders around the world, who must balance the need to protect public health with spiritual and emotional needs. Despite these obstacles, religious leaders have risen to the occasion and implemented protective measures for their communities, including social isolation and vaccination encouragement. Through online counseling, virtual gatherings, and practical assistance, they have also provided spiritual and emotional support. Lessons learned include the significance of adapting to new technologies, putting public health and safety first, and the vital role of religious institutions in providing community and social support during times of crisis.